LGG-22. TREATMENT OUTCOME AND LONG-TERM HEALTH DEFICITS OF PATIENTS WITH LOW-GRADE GLIOMA DIAGNOSED DURING THE FIRST YEAR OF LIFE. Issue 2 (22nd June 2018) - Liu, Anthony; Hastings, Camden; Wu, Shengjie; Bass, Johnnie K; Heitzer, Andrew; Ashford, Jason; Vestal, Robert; Hoehn, Mary; Chiang, Jason; Ghazwani, Yahya; Acharya, Sahaja; Conklin, Heather; et al.
Abstract: Low-grade glioma (LGG) diagnosed during infancy is associated with unique clinical profile and challenges in management. Morbidities in long-term survivors are not well described. We retrospectively reviewed patients with LGG diagnosed before 12 months of age managed at St. Jude Children's Research Hospital from 1986-2013. Altogether, 51 patients were identified, 31 were males, 7 had neurofibromatosis. Primary tumor locations were hypothalamic/optic pathway (n=31), cerebral (n=6), brainstem (n=6), cerebellar (n=4), and spinal (n=4); 12 patients experienced metastasis. At diagnosis, 41 patients required active intervention: surgical resection (n=23; 5 with adjuvant chemotherapy), chemotherapy (n=16), radiation (n=1), or chemotherapy and radiation (n=1). Throughout the course of disease, 39/51 patients required chemotherapy (median number of regimens: 2; range, 1-13); 21 required radiation (focal=19; CSI=2); and 41 received tumor-directed surgeries (median number of operations: 2; range, 1-6). Twenty-nine patients had grade I tumors; 6 had grade II tumors, and 6 had tumors that could not be definitively graded. CSF diversion was performed in 31 patients. The mean duration of follow-up was 11.5y (range, 0.16-29.19y). Thirty-five patients experienced progression (median progressions: 2; range, 1-18), and 9 patients died (progression=3, malignant transformation=3, shunt infection=1, leukemia=1, unknown=1). The respective 5-year, 10-year, and 20-year overall-survival rates were 91.6 ± 4%, 86.4 ± 5.2%, and 71.9 ± 8.8%. Adverse health issues were documented in 49/51 patients; common morbidities included hearing impairment (n=15), visual impairment (n=31), neurocognitive deficit (n=31), hemiplegia/paraplegia (n=19), endocrinopathy (n=31), and cerebrovascular disease (n=15). LGG diagnosed during infancy was almost universally associated with long-term morbidities and survivors should be prioritized for multi-disciplinary surveillance.